Antiseizure medication in early nervous system development. Ion channels and synaptic proteins as principal targets - Castro, Patricio A.; Pinto-Borguero, Ingrid; Yévenes, Gonzalo E.; Moraga-Cid, Gustavo; Fuentealba, Jorge (Frontiers in Pharmacology, 2022)
The main strategy for the treatment of epilepsy is the use of pharmacological agents known as antiseizure medication (ASM). These drugs control the seizure onset and improves the life expectancy and quality of life of patients. Several ASMs are contraindicated during pregnancy, due to a potential teratogen risk. For this reason, the pharmacological treatments of the pregnant Women with Epilepsy (WWE) need comprehensive analyses to reduce fetal risk during the first trimester of pregnancy. The mechanisms by which ASM are teratogens are still under study and scientists in the field, propose different hypotheses. One of them, which will be addressed in this review, corresponds to the potential alteration of ASM on ion channels and proteins involved in relevant signaling and cellular responses (i.e., migration, differentiation) during embryonic development. The actual information related to the action of ASM and its possible targets it is poorly understood. In this review, we will focus on describing the eventual presence of some ion channels and synaptic proteins of the neurotransmitter signaling pathways present during early neural development, which could potentially interacting as targets of ASM. This information leads to elucidate whether these drugs would have the ability to affect critical signaling during periods of neural development that in turn could explain the fetal malformations observed by the use of ASM during pregnancy.